A systematic review of rehabilitation and exercise recommendations in oncology guidelines. (27th October 2020) - Stout, Nicole L.; Santa Mina, Daniel; Lyons, Kathleen D.; Robb, Karen; Silver, Julie K.
Abstract: Guidelines promote high quality cancer care. Rehabilitation recommendations in oncology guidelines have not been characterized and may provide insight to improve integration of rehabilitation into oncology care. This report was developed as a part of the World Health Organization (WHO) Rehabilitation 2030 initiative to identify rehabilitation‐specific recommendations in guidelines for oncology care. A systematic review of guidelines was conducted. Only guidelines published in English, for adults with cancer, providing recommendations for rehabilitation referral and assessment or interventions between 2009 and 2019 were included. 13840 articles were identified. After duplicates and applied filters, 4897 articles were screened. 69 guidelines were identified with rehabilitation‐specific recommendations. Thirty‐seven of the 69 guidelines endorsed referral to rehabilitation services but provided no specific recommendations regarding assessment or interventions. Thirty‐two of the 69 guidelines met the full inclusion criteria and were assessed using the AGREE II tool. Twenty‐one of these guidelines achieved an AGREE II quality score of ≥ 45 and were fully extracted. Guidelines exclusive to pharmacologic interventions and complementary and alternative interventions were excluded. Findings identify guidelines that recommend rehabilitation services across many cancer types and for various consequences of cancer treatment signifying that rehabilitation is a recognized component of oncology care. However, these findings are at odds with clinical reports of low rehabilitation utilization rates suggesting that guideline recommendations may be overlooked. Considering that functional morbidity negatively affects a majority of cancer survivors, improving guideline concordant rehabilitative care could have substantial impact on function and quality of life among cancer survivors.